ASEAN beyond the regional crisis challenges and initiatives - Mya Than (Institute of Southeast Asian Studies, 1999)
As the regional and financial economic crisis has bottomed out and the ASEAN countries are on the recovery path, this volume seeks to carry out a post-mortem on the crisis to evaluate the sustainability of the recovery and the long-term direction of the ASEAN economies.